Study of Death among Children below five Years of Age and Its Relationship with Person Conducting Delivery and Place of Residence. Using Verbal Autopsy as a Tool in Deharadun - Sushil Dalal1 , Kiran Pande2 , Neetu Pippet3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Substantial reduction in child mortality has occurred in low income and middle income countries in the late 20th century but more than ten million children younger than five years still die every year , one of the important factor which has been observed in under five mortality is the person conducting the delivery . Keeping this in view, this study was conducted to find out relation in-between child mortality of under-five years of age and its relation with person conducting delivery and place of residence. using verbal autopsy as a tool in Deharadun. Methodology: The survey was done on all the houses of the deceased children residing in our field practice areas by visiting their houses. Results: Among the 83 deaths reported most of the deaths were conducted by daies and relatives. Conclusion: Our study shows that delivery conducted by qualified personnel greatly help in reducing the under-five mortality rate